A PPP (PRESENTATION, PRACTICE, AND PRODUCTION) PHASE METHOD OF TEACHING SPEAKING TO UNIVERSITY STUDENTS - Adi Yusuf (Universitas Pesantren Tinggi Darul Ulum Jombang, 2015)
Teaching speaking is considered as the “interesting and challenging activity”. Indeed, it needs various ways in order to make students “active in speaking” during the class. This article would like to present the three phases, namely a PPP (Presentation, Practice, and Production) method in “teaching speaking to university students”. The fundamental principles of using this method is that the “students are smart and creative”. Eventhough, they are considered as “intelligent and creative”, teachers still need to guide or control them to anticipate any errors made by the students. Furthermore, it is important for teachers to know when to give “instant correction” in class. When the class is focused on accuracy, teachers can give an “instant correction”. On the other hand, when it is focused on “fluency”, it is not suggested that teachers give “instant correction” and this may interfere with the goals of activity. Keywords: Presentation, Practice, Production, accuracy, fluency Abstrak Mengajar kelas speaking bisa dianggap sebagai aktivitas yang menarik dan menantang. Berbagai cara benar-benar perlu dilakukan untuk membuat para siswa aktif dalam berbicara selama pelajaran. Artikel ini membahas tentang tiga tahapan, yaitu sebuah metode PPP (Presentation, Practice, and Production) yang diterapkan dalam “mengajar speaking” pada mahasiswa. Landasan dalam menggunakan metode ini adalah bahwa mahasiswa pandai dan kreatif. Meskipun, demikian pengajar masih perlu “membimbing atau mengontrol” mereka untuk mengantisipasi adanya kesalahan. Di samping itu, pengajar harus tahu kapan waktu yang tepat untuk memberikan “koreksi langsung” di kelas. Ketika kelas sedang difokuskan pada “ketepatan”, pengajar bisa memberikan “koreksi langsung”. Sebaliknya, ketika kelas sedang difokuskan pada “kepasihan/ kelancaran”, sebaiknya pengajar tidak memberikan “koreksi langsung” dan hal ini bisa mengganggu tujuan aktifitas kelas. Kata kunci: Presentation, Practice, Production, accuracy, fluency